2017
DOI: 10.1111/acel.12593
|View full text |Cite
|
Sign up to set email alerts
|

HIV and drug abuse mediate astrocyte senescence in a β‐catenin‐dependent manner leading to neuronal toxicity

Abstract: SummaryEmerging evidence suggests that cell senescence plays an important role in aging‐associated diseases including neurodegenerative diseases. HIV leads to a spectrum of neurologic diseases collectively termed HIV‐associated neurocognitive disorders (HAND). Drug abuse, particularly methamphetamine (meth), is a frequently abused psychostimulant among HIV+ individuals and its abuse exacerbates HAND. The mechanism by which HIV and meth lead to brain cell dysregulation is not entirely clear. In this study, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 45 publications
0
31
1
Order By: Relevance
“…Given that premature senescence from HAART drugs and HIV proteins has been linked to comorbidities in non‐CNS cell types (Beaupere et al, ; Nacarelli, Azar, & Sell, ), astrocyte senescence in response to these stimuli could be a contributor to HAND. Indeed, a very recent study demonstrated that human astrocytes infected with an HIV plasmid underwent premature senescence (Yu et al, ). Conditioned media from these senescent astrocytes induced neuronal apoptosis suggesting that senescent astrocytes could have an adverse effect on the CNS microenvironment in the context of HIV and HAND.…”
Section: Neurodegenerative Disease and Astrocyte Senescencementioning
confidence: 99%
“…Given that premature senescence from HAART drugs and HIV proteins has been linked to comorbidities in non‐CNS cell types (Beaupere et al, ; Nacarelli, Azar, & Sell, ), astrocyte senescence in response to these stimuli could be a contributor to HAND. Indeed, a very recent study demonstrated that human astrocytes infected with an HIV plasmid underwent premature senescence (Yu et al, ). Conditioned media from these senescent astrocytes induced neuronal apoptosis suggesting that senescent astrocytes could have an adverse effect on the CNS microenvironment in the context of HIV and HAND.…”
Section: Neurodegenerative Disease and Astrocyte Senescencementioning
confidence: 99%
“…By secreting SASP factors, the SASP can trigger immune surveillance of senescent cells ( Xue et al, 2007 ), enforce cell cycle arrest ( Acosta et al, 2008 ; Bartek et al, 2008 ), and alter tissue microenvironments ( Tchkonia et al, 2013 ). Evidence also suggest that the SASP can induce paracrine senescence in normal cells ( Kuilman et al, 2008 ; Yu et al, 2017 ) via the SASP proteins IGFBP7 ( Wajapeyee et al, 2008 ) and IL-6 ( Acosta et al, 2013 ), which goes further in explaining how the SASP alter tissue microenvironments ( González-Puertos et al, 2015 ). The NISIM, by integrating the SASP, could perhaps help elucidate some of the antecedent aspects regarding the induction of age-related pathologies ( Figures 2 , 3 ).…”
Section: Applying the Model: Neurodegenerative Disease And Cancermentioning
confidence: 99%
“…Astrocytes are highly specialized cells in the CNS with well-established immune and non-immune functions including glutamate uptake, maintenance of the blood brain barrier (BBB), and secretion of immune modulators, including IL-6 [20,[39][40][41][42][43][44][45]. We previously reported that astrocytes have robust expression of the Wnt/β-catenin signaling pathway and its disrupting, in response to inflammation and or viral infection, leads to dysregulation of key functions of astrocytes including induction of astrocyte senescence [41,46]. IL-6 is a hallmark cytokine associated with the senescence associated secretory phenotype (SASP), a collection of cytokines and other secretory factors secreted under cellular senescence [47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%